An evaluation of anti-cancer activities of Hyaenanche Globosa Lamb. (Euphorbiaceae) and Maytenus Procumbens (L.F.) Loes. (Celastraceae) - Ostad, Seyed Nasser (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.